Os efeitos dos custos das transações comerciais e do livre comércio no mercado internacional da soja - Caetani, Maria Inês Rosa da Rocha (2014)
This study analyzes and discusses the impact of the costs of doing business and tariff barriers and subsidies in international trade in soybeans. To achieve this goal, we use a partial equilibrium model formulated as a Mixed Complementarity Problem - MCP - which allows the inclusion of transaction costs and trade policies, tariffs and subsidies in addition to the construction of scenarios. Three simulations are constructed to test the impacts: first eliminate the costs of transactions in the second, retire trade policies and the third is testing a 20% increase in the consumption of soy. The results show that the elimination of transaction costs favors Brazil, Argentina and China increased exports and increasing imports from the United States and Europe. The countries of the rest of the world are most benefited by the condition of the free market. In general, the impact of transaction costs in the soy market depend on adopted and the characteristics of production and consumption policies of each region, and may not be opposites or trade policies. The scenario of increase in world consumption shows that with the rate of consumption of soy at the same levels of the years 2009 to 2011 and with the same pattern of transaction costs and trade policies, Brazil is unique among major producers they can not increase their participation in world exports of soybeans.